Early adverse emotional response to childbirth in Turkey: The impact of maternal attachment styles and family support - ÖZEK, EREN; ÖZDEN, İDİL; AKMAN, MEHMET (TAYLOR & FRANCIS LTD, 2008)
Early adverse emotional response which is often detected in the form of depressive symptoms is a predictor of postpartum depression following the birth. The aim of our study is to highlight contextual and individual factors that have an impact on mothers' depressive symptoms during the early postpartum period. One hundred mothers participated in the study. Maternal depressive symptoms were screened by Edinburgh Postpartum Depression Scale (EPDS), and maternal anxiety level was assessed by State-Trait Anxiety Inventory (STAI) at early postpartum period (7-10 days). The Multidimensional Scale of Perceived Social Support (MSPSS) was used for the assessment of maternal social support. The Adult Attachment Scale (AAS) was used to determine the attachment style of the mother. The mean EPDS score of mothers who live in extended families is found to be significantly lower than mothers who live in nuclear families (extended families 7.13 +/- 7.39, nuclear families 11.77 +/- 5.96, p=0.006). Significant positive correlations were found between EPDS total scores and ambivalent attachment style group (r=.0436, p=.000), and avoidant attachment style group (r=.328, p=.001). The level of perceived family support also showed a negative correlation with EPDS total score (r=-.363, p=.000). The regression of EPDS total score with ambivalent attachment style and state anxiety level are positively predicted and the level of perceived family support and existence of wider social network negatively predict the EPDS total score in the first postpartum week. Maternal attachment patterns, living with the extended family and existence of family support have an important impact on early postpartum emotional adaptation. Early intervention strategies should count towards these individual and contextual factors when designing screening and preventive interventions for postpartum depression.
Keywords: emotional response to childbirth; maternal attachment style; family support; POSTPARTUM DEPRESSION; POSTNATAL DEPRESSION; RISK-FACTORS; BLUES; PREVALENCE; SYMPTOMATOLOGY; PREVENTION; PREGNANCY; DELIVERY; SEEKING